東南極ドームふじにおける、層構造をなすフィルンの変態とその空間可変性 - 藤田, 秀二; 東, 久美子; 飯塚, 芳徳; 平林, 幹啓; 堀, 彰; 望月, 優子; 本山, 秀明; Fujita, Shuji; Goto-Azuma, Kumiko; Hirabayashi, Motohiro; Hori, Akira; Iizuka, Yoshinori; et al. (2014)
conference object